Psychometric properties of the Greek Inventory of Personality Organization - Brief (IPO-Brief-GR) in a community sample of emerging adults - Aikaterini Malafanti; Eleni Giannouli; Yotsidi, Vasiliki; Sideridis, Georgios; Galanaki, Evangelia P.; John F. Clarkin; Mark F. Lenzenweger; Malogiannis, Ioannis (Current Research in Behavioral Sciences, 2024)
Several studies have evaluated different versions of the Inventory of Personality Organization (IPO) around the world and some shortened versions of the instrument have also been constructed. The aim of this study was to develop the first brief Greek-language version of the IPO (IPO-Brief-GR) to be used for clinical screening and research purposes regarding personality pathology defined according to Kernberg's object relations model of personality organization. Data were collected from a community sample of 543 Greek emerging adults aged 18–29 years (M = 21.45, SD = 2.51) with the 83-item IPO, from which a 30-item version was constructed, based on confirmatory factor analysis of the full measure. The psychometric properties of the IPO-Brief-GR were then examined. Confirmatory factor analyses indicated that a four-factor structure best fitted the data, that is, primitive defenses/identity diffusion, reality testing, aggression, and moral values. Criterion validity and internal consistency reliability were also supported. Measurement invariance across gender using an exact protocol approach (i.e., configural, metric, scalar) was found allowing latent mean comparisons. These preliminary findings support the reliability and validity of the IPO-Brief-GR for the assessment of borderline personality organization and indicate the need for further research into the psychometric properties and clinical utility of this measure.